Case report: Successful management of a refractory double-expressor diffuse large B-cell lymphoma patient under the guidance of in vitro high-throughput drug sensitivity test - Xing, Lijie; Wang, Hui; Liu, Dan; He, Qiang; Li, Zengjun (Frontiers in Oncology, 2023)
Introduction: Double expressor diffuse large B-cell lymphoma (DEL), harboring double expression of MYC and BCL2, have an inferior prognosis following standard first-line therapy with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone (R-CHOP). We initiated a clinical trial to treat newly diagnosed DEL with R-CHOP plus BTK inhibitor (BTKi) zanubrutinib (ZR-CHOP) and achieved a high complete response (CR) rate, while four patients progressed during therapy, one of them carrying ATM and CD58 mutations. We applied in vitro high-throughput drug sensitivity test for the prediction of clinical responses to different drugs in this patient. Case presentation: We report a 30-year-old female patient diagnosed with stage III (DEL), with ATM and CD58 mutations. The patient achieved partial response (PR) after two cycles of ZR-CHOP and remained PR after four cycles of ZR-CHOP, while the disease progressed after six cycles of ZR-CHOP. High-throughput drug screening using a panel of 117 compounds identified a range of therapies with efficacy in this patient. The primary tumor cells showed moderately sensitive to bortezomib, thalidomide, and gemcitabine as a single agent, and VTD (Bortezomib, thalidomide, dexamethasone) as a combined regimen. The patient was treated with two cycles of VTD regimen (Bortezomib 1.3mg/m2, d1, 4, 8, 11; thalidomide 100mg, d1-21; dexamethasone 20mg, d1, 2, 4, 5, 8, 9), and achieved PR with only a small lesion left. Then another two cycles of VTD plus gemcitabine were administered, and the patient achieved CR. Stem cells were mobilized, and autologous hematopoietic stem cell transplantation was carried out afterward. The patient remained CR for more than 3 months after transplantation. Conclusion: In this article, we present a first-line chemo-resistant DEL patient with ATM and CD58 mutations, who was treated successfully with VTD plus gemcitabine under the guide of in vitro high-throughput drug sensitivity test.